PULMONARY SEQUESTRATION – RARE FINDINGS - DR. SUBRAMANIAN S.,; DR. APAR JINDAL,; DR. ABUBACKER SULAIMAN,; DR. N. MEENAKSHI, (International Journal of Pharma and Bio Sciences, 2015)
Pulmonary sequestration is a developmental disorder characterized by nonfunctioning abnormal pulmonary parenchyma that has no connection with the tracheobronchial tree and receiving blood supply from a systemic artery. Two forms have been described, Intralobar (within the normal lung visceral pleura), and Extralobar (totally separate with its own pleural covering). We present a case of a 48 year old female with recurrent hemoptysis for one year. Chest radiograph demonstrated a well defined opacity in the right lower zone. CECT thorax showed a round heterogeneously enhancing mass in Right Lower Lobe Lateral Basal Segment. 3D reconstruction imaging revealed an anomalous artery arising from the Right Renal Artery supplying the mass and venous drainage into the Inferior Pulmonary Vein establishing a diagnosis of Right Lower Lobe Intralobar Sequestration. The rare findings in our case were the anomalous arterial supply from a branch of right renal artery and sequestration in Right Lower Lobe.